Bacterial natural products in the fight against mosquito-transmitted tropical diseases. Issue 3 (23rd September 2019) - Saraiva, Raúl G.; Dimopoulos, George
Abstract : In this review, we discuss the merits of using bacterial metabolites – including those secreted by the mosquito microbiota – to combat malaria and filariasis, as well as dengue fever and other arboviral diseases. Abstract : Covering: up to 2019 Secondary metabolites of microbial origin have long been acknowledged as medically relevant, but their full potential remains largely unexploited. Of the countless natural compounds discovered thus far, only 5–10% have been isolated from microorganisms. At the same time, while whole-genome sequencing has demonstrated that bacteria and fungi often encode natural products, only a few genera have yet been mined for new compounds. This review explores the contributions of bacterial natural products to combatting infection by malaria parasites, filarial worms, and arboviruses such as dengue, Zika, Chikungunya, and West Nile. It highlights how molecules isolated from microorganisms ranging from marine cyanobacteria to mosquito endosymbionts can be exploited as antimicrobials and antivirals. Pursuit of this mostly untapped source of chemical entities will potentially result in new interventions against these tropical diseases, which are urgently needed to combat the increase in the incidence of resistance.